2016
DOI: 10.3122/jabfm.2016.01.150128
|View full text |Cite
|
Sign up to set email alerts
|

Time to Remission for Depression with Collaborative Care Management (CCM) in Primary Care

Abstract: Background: Collaborative care management (CCM) has been shown to have superior outcomes to usual care (UC) for depressed patients with a fixed end point. This study was a survival analysis over time comparing CCM with UC using remission (9-item Patient Health Questionnaire [PHQ-9] score <5) and persistent depressive symptoms (PDSs; PHQ-9 score >10) as end points.Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…The patients in our study were secure in the knowledge that the CM collaborated with others and would help them get health care when needed. Also, previous studies have shown how important collaborative care management is in supporting recovery for patients with depression (Garrison et al, 2016;Thota et al, 2012). This is also important from a primary care perspective, where access to care (Starfield, 2009) and continuity are vital (Starfield, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients in our study were secure in the knowledge that the CM collaborated with others and would help them get health care when needed. Also, previous studies have shown how important collaborative care management is in supporting recovery for patients with depression (Garrison et al, 2016;Thota et al, 2012). This is also important from a primary care perspective, where access to care (Starfield, 2009) and continuity are vital (Starfield, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that individual support and collaborative care are two factors strongly contributing to recovery for persons with depression, while also being cost‐effective (Donohue et al, ; Garrison et al, ). The patients in our study emphasized the importance of the CM's collaboration, especially with the GP, so that the number of care contacts could be reduced over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that recurrent depression has slower remission [29], but according to the similar frequency of maintenance antidepressant medication in both intervention and TAU groups at inclusion, we can assume that the rate of recurrent depression disorder was the same in both arms. Further, the high number of outcomes, assessed at baseline and at 3, 6, and 12 months, necessitated multiple statistical comparisons, thus increasing the possibility of type I errors.…”
Section: Discussionmentioning
confidence: 99%
“…These two factors can facilitate better depression outcomes [2931]. Depression is complex, and the outcome of treatment often depends on the GP’s ability to connect with the patient during the consultation and her/his ability to choose proper treatment in agreement with the patient.…”
Section: Discussionmentioning
confidence: 99%